(untitled) (Encuentros, 2019)
The objective of this work is to identify the main variables that generate difficulties in the learning of undergraduate students in Logic and Algorithms I and II in the Faculty of Engineering of the University of Amazonia. The research was carried out through a case study approach and a descriptive analysis of the presented situation, evaluating the competences of autonomous learning through surveys. In this sense, in developing the work, a diagnosis was established to generate strategies and take action on the part of the academic directives Key words: repetition; autonomous learning competences; educational development competences.